Effects of peripheral administration of lipopolysaccharide on chronic sickness responses in TRPM8-deficient mice. (1st November 2022) - Horikawa, Ririka; Oe, Yuzuki; Fujii, Rena; Kasuga, Rika; Yoshimura, Ryoichi; Miyata, Seiji
Highlights: TRPM8 KO mice show longer-lasting hypothermia by LPS administration. TRPM8 KO mice reveal longer-lasting decrease in motor activity by LPS treatment. TRPM8 KO mice exhibit longer-lasting decline in food intake by LPS treatment. TRPM8 KO mice show longer-lasting decrease of leucocyte number by LPS treatment. Abstract: Transient receptor potential melastatin 8 (TRPM8) is a cold-sensing thermoreceptor cation channel; however, its functional role in endotoxin-induced neuroinflammation remains unclear. In the present study, we investigated chronic sickness responses in TRPM8 knockout (KO) mice during lipopolysaccharide (LPS)-induced sepsis. The intraperitoneal administration of 5 mg/kg LPS generated longer-lasting hypothermia in TRPM8 KO mice than in wild-type (WT) mice. TRPM8 KO mice also exhibited longer-lasting declines in locomotor activity, body weight, and food and water intakes than WT mice upon LPS administration. In addition, LPS-induced decreases in the numbers of leucocytes and lymphocytes that persisted for a longer time in TRPM8 KO mice than in WT mice. The present results indicate TRPM8 attenuated chronic sickness responses in endotoxin-induced sepsis.